Phosphatidylserine decarboxylase is critical for the maintenance of skeletal muscle mitochondrial integrity and muscle mass - Ahrathy Selathurai; Greg M. Kowalski; Shaun A. Mason; Damien L. Callahan; Victoria C. Foletta; Paul A. Della Gatta; Angus Lindsay; Steven Hamley; Gunveen Kaur; Annie R. Curtis; Micah L. Burch; Teddy Ang; et al. (Elsevier, 2019)
Objective: Phosphatidylethanolamine (PtdEtn) is a major phospholipid in mammals. It is synthesized via two pathways, the CDP-ethanolamine pathway in the endoplasmic reticulum and the phosphatidylserine (PtdSer) decarboxylase (PSD) pathway in the mitochondria. While the CDP-ethanolamine pathway is considered the major route for PtdEtn synthesis in most mammalian tissues, little is known about the importance of the PSD pathway in vivo, especially in tissues enriched with mitochondria such as skeletal muscle. Therefore, we aimed to examine the role of the mitochondrial PSD pathway in regulating PtdEtn homeostasis in skeletal muscle in vivo. Methods: To determine the functional significance of this pathway in skeletal muscle in vivo, an adeno-associated viral vector approach was employed to knockdown PSD expression in skeletal muscle of adult mice. Muscle lipid and metabolite profiling was performed using mass spectrometry. Results: PSD knockdown disrupted muscle phospholipid homeostasis leading to an ∼25% reduction in PtdEtn and an ∼45% increase in PtdSer content. This was accompanied by the development of a severe myopathy, evident by a 40% loss in muscle mass as well as extensive myofiber damage as shown by increased DNA synthesis and central nucleation. In addition, PSD knockdown caused marked accumulation of abnormally appearing mitochondria that exhibited severely disrupted inner membrane integrity and reduced OXPHOS protein content. Conclusions: The PSD pathway has a significant role in maintaining phospholipid homeostasis in adult skeletal muscle. Moreover, PSD is essential for maintenance of mitochondrial integrity and skeletal muscle mass. Keywords: Phospholipids, Phosphatidylethanolamine, Phosphatidylserine, Mitochondria, Skeletal muscle, Atrophy